IMPLEMENTATION OF WATERFRONT MANAGEMENT POLICY BASED ON MAYOR REGULATION NO. 26 OF 2019 CONCERNING THE MANAGEMENT AND SUPERVISION OF WATERFRONT AREAS IN THE CITY OF PONTIANAK - Yula Pratara; S.Y. Pudjianto; Jumadi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This thesis examines the implementation of the Waterfront Management Policy in Pontianak City based on Mayoral Regulation Number 26 of 2019. The study uses a qualitative approach with Marilee S. Grindle's policy implementation theory, which examines the policy content and the context of its implementation. The findings indicate that the policy implementation has not fully complied with regulations, mainly due to the absence of a mechanism for enforcement against violating street vendors, resulting in the Waterfront facilities being widely used for selling. In addition, budget limitations due to efficiency policies have an impact on supervision. Another obstacle arises from vendors' resistance to relocation, which is based on customary land claims. Suggestions include revising the Mayoral Regulation by adding an article on street vendor enforcement, implementing an efficient operating scheduling system, and holding a dialogue forum between the government, the community, and stakeholders to support more effective policy implementation.